Bilingual Digital Storytelling as a Method to Enhance Children’s English Language Skills: A Micro-Linguistic Perspective - Kurniawan, Mozes; Wijayaningsih, Lanny (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
English language learning in early childhood has become a priority in 21st-century education due to the growing global demand for early foreign language competence. However, this process still encounters several challenges, including limited interest, a lack of suitable learning media, and linguistic barriers such as morphological recognition that hinder children’s understanding of word structures and meanings. This study aims to enhance young learners’ English vocabulary and morphological awareness through the implementation of Bilingual Digital Storytelling (BDS) as a method of interactive and engaging language instruction. A descriptive qualitative design with a Classroom Action Research (CAR) approach was employed at STB Kindergarten, involving children aged 4 to 6 years as participants. Data were collected through classroom observations and interviews, supported by systematically designed observation guides and instruments. The findings revealed that the application of Bilingual Digital Storytelling significantly improved children’s English vocabulary mastery from an initial 0% recognition rate to 100% in the second cycle. Furthermore, the method enhanced children’s morphological awareness, particularly in identifying word forms and meanings. In addition, BDS effectively increased learner engagement and attention span, making the learning process more enjoyable and participatory.